Analysis of the Effect of the Role of Credit and Promotion on Electronic Furniture Purchases - Wardatul Aini Harahap; Risa Kartika Lubis (Journal of Economics and Business (JECOMBI), 2021)
This study aims to determine the effect of the role of credit and promotion on the purchase of electronic furniture in the Metro Lubuk Pakam and to determine the dominant variable on the decision to purchase electronic furniture in the Metro Lubuk Pakam. The method used in this research is descriptive quantitative method while data collection uses the method of observation, interviews, documentation and questionnaires. The sample used in this study were employees of the Metro Lubuk Pakam with a total sample of 60 people. The results of this study indicate that the independent variables, namely the Role of Credit and Promotion (X1), the Electronic and Furniture (Y1) factors, have a positive and significant effect on the decision to purchase electronic furniture in Metro Lubuk Pakam.